2021
DOI: 10.1021/acs.jpcc.1c04479
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous 17O Dynamic Nuclear Polarization of Gd-Doped CeO2 from 100 to 370 K

Abstract: 17O NMR is an invaluable tool to study the structure and dynamics of oxide materials but remains challenging to apply in many systems. Even with isotopic enrichment, studies of samples with low masses and/or concentrations of the active species, such as thin films or interfaces, are limited by low sensitivity. Here, we show how endogenous dynamic nuclear polarization (DNP) can dramatically improve the sensitivity in the oxide-ion conductor Gd-doped CeO2, with a 17O enhancement factor of 652 at 100 K. This is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 70 publications
0
19
0
Order By: Relevance
“…30 Endogenous Gd(III) dopants have been used to hyperpolarize nuclei in inorganic solids such as metal oxides, 31,32 glasses, 33 and battery electrode materials; 34−36 for example, recently, Gd(III) has been shown to provide large 17 O solid effect DNP enhancements of 652 at 100 K and 320 at room temperature in 17 enriched ceria. 32 These high enhancements were attributed to the cubic environment of the metal in the ceria lattice and to the relatively small magnitude of the higher-order electrostatic multipoles, that in turn lead to relatively narrow EPR linewidths which can be easily saturated under DNP conditions. On the other hand, Griffin and co-workers demonstrated that the molecular Gd complexes [Gd(dota) (H 2 O)] − and [Gd(dtpa) (H 2 O)] 2− , hereafter abbreviated as Gd(dota) and Gd(dtpa), respectively (Figure 1A), could be used as exogenous polarizing agents in MAS DNP, 27 where Gd(dota) exhibited a relatively good solid effect 1 H DNP enhancement.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 Endogenous Gd(III) dopants have been used to hyperpolarize nuclei in inorganic solids such as metal oxides, 31,32 glasses, 33 and battery electrode materials; 34−36 for example, recently, Gd(III) has been shown to provide large 17 O solid effect DNP enhancements of 652 at 100 K and 320 at room temperature in 17 enriched ceria. 32 These high enhancements were attributed to the cubic environment of the metal in the ceria lattice and to the relatively small magnitude of the higher-order electrostatic multipoles, that in turn lead to relatively narrow EPR linewidths which can be easily saturated under DNP conditions. On the other hand, Griffin and co-workers demonstrated that the molecular Gd complexes [Gd(dota) (H 2 O)] − and [Gd(dtpa) (H 2 O)] 2− , hereafter abbreviated as Gd(dota) and Gd(dtpa), respectively (Figure 1A), could be used as exogenous polarizing agents in MAS DNP, 27 where Gd(dota) exhibited a relatively good solid effect 1 H DNP enhancement.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Gd­(III) complexes also possess favorable EPR properties such as a quenched spin–orbit coupling and weak hyperfine couplings with 155/157 Gd, in comparison to other paramagnetic metal ions . Endogenous Gd­(III) dopants have been used to hyperpolarize nuclei in inorganic solids such as metal oxides, , glasses, and battery electrode materials; for example, recently, Gd­(III) has been shown to provide large 17 O solid effect DNP enhancements of 652 at 100 K and 320 at room temperature in 17 O-enriched ceria . These high enhancements were attributed to the cubic environment of the metal in the ceria lattice and to the relatively small magnitude of the higher-order electrostatic multipoles, that in turn lead to relatively narrow EPR linewidths which can be easily saturated under DNP conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] DNP enhances nuclear magnetization through the microwave (MW)-driven transfer at cryogenic temperatures of electron spin polarization to nuclei via paramagnetic centers, which are typically referred to as polarizing agents (PAs). In principle, whereas PAs can either be contained in (endogenous) or added to (exogenous) the material under investigation, the best DNP sensitivity enhancements obtained so far have been observed when using exogenous PAs, although there are some notable exceptions, [12][13][14][15] including recent work where endogenous radicals were generated in the sample by γ-ray irradiation. [16,17] As a matter of fact, the design of efficient PAs has been the subject of extensive research over the last few years, which has led to the synthesis of a wide range of biradicals exhibiting increasingly complex molecular structures (e.g., TOTAPOL, [18] bTbK, [19] TEKPol, [20] AMUPol, [21] HyTEK2, [22] cAsymPol-POK, [23] and nitroxyl-trityl biradicals [24] ).…”
Section: Introductionmentioning
confidence: 99%
“…Gd 3+ is of particular interest, as it offers large 1 H NMR signal enhancements ϵ of ∼19 for [Gd­(dota)­(H 2 O)] − and ∼37 for [Gd­(tpcatcn)] complexes at 9.4 T . High-spin metal ions also allow for endogenous hyperpolarization where intrinsic ions are contained in the samples as dopants (in inorganic solids) such as Mn 2+ -doped Li 4 Ti 5 O 12 or (in oxide glasses) such as Gd 3+ -doped lithium silicate, lithium borate, and zinc phosphate for bulk signal enhancements, in Gd 3+ -doped CeO 2 nanocomposite thin films on SrTiO 3 for detailed study of material interfaces, and in spin-labels as chelator tags …”
Section: Introductionmentioning
confidence: 99%
“…More recently, inspired by paramagnetic transition metal and lanthanide complexes used for in vivo magnetic resonance imaging (MRI) applications, 38,39 high-spin metal ions have shown potential 40−44 as alternatives to tailored nitroxide-based biradical PAs for specific applications, 1 H DNP, or the direct DNP of lower gamma nuclear spins. Gd 3+ is of particular interest, as it offers large 1 H NMR signal enhancements ϵ of ∼19 for [Gd(dota)(H 2 O)] − and ∼37 for [Gd(tpcatcn)] complexes at 9.4 T. 43 High-spin metal ions also allow for endogenous hyperpolarization where intrinsic ions are contained in the samples as dopants (in inorganic solids) such as Mn 2+ -doped Li 4 Ti 5 O 12 45 or (in oxide glasses) such as Gd 3+ -doped lithium silicate, lithium borate, and zinc phosphate 46 for bulk signal enhancements, in Gd 3+ -doped CeO 2 nanocomposite thin films on SrTiO 3 for detailed study of material interfaces, 47 and in spin-labels as chelator tags. 41 An exciting opportunity for MAS DNP consists of utilizing an "off-the-shelf" paramagnetic metal ion species as a PA that is easily affordable and does not require any chemical synthesis.…”
Section: ■ Introductionmentioning
confidence: 99%